Brazilian Chronic Dialysis Survey 2016 - Sesso,Ricardo Cintra (2017)
Abstract Introduction: National chronic dialysis data are important for the treatment planning. Objective: To report data of the annual survey of the Brazilian Society of Nephrology about chronic kidney disease patients on dialysis in July 2016. Methods: A survey based on data of dialysis centers from the whole country. The data collection was performed by using a questionnaire filled out on-line by the dialysis centers. Results: 309 (41%) of the dialysis units in the country answered the questionnaire. In July 2016, the total estimated number of patients on dialysis was 122,825. The estimated prevalence and incidence rates of chronic maintenance dialysis were 596 (range: 344 in the North region and 700 in the Southeast) and 193 patients per million of population (pmp), respectively. The annual incidence rate of patients with diabetic nephropathy was 79 pmp. The annual gross mortality rate was 18.2%. For prevalent patients, 92% were on hemodialysis and 8% on peritoneal dialysis, and 29,268 (24%) were on a waiting list of renal transplant. A venous catheter was the vascular access for 20.5% of the hemodialysis patients. The prevalence rates of positive serology for hepatitis B and C showed a tendency to reduce from 2013 (1.4% and 4.2%, respectively) to 2016 (0.7% and 3.7%, respectively). Conclusion: The absolute number and the prevalence and incidence rates of patients on dialysis continue to rise steadily; the gross mortality rate remained stable. Regional inequities are evident in these rates.